Assessment of resistanse to Globodera rostochiensis (Ro-1) of newly created potato breeding material - Sigareva, D.; Bondar, T.; Nikishicheva, K. (Quarantine and plant protection, 2024)
Goal. Selection among breeding samples of potatoes, created by four breeding institutions, resistant to the golden potato cyst-forming nematode Globodera rostochiensis (Ro-1). Methods. The assessment of nematode resistance was carried out according to «Regulations on the procedure for testing potato varieties and hybrids for resistance to ... golden potato cyst nematode» (1993). Results. Potato breeding material was evaluated for resistance to Globodera rostochiensis (Ro-1). Of the 640 samples that were sent from four breeding institutions (JSC SIA «Chernigivelitkartoplia», the Polissia branch of the Institute of Potatoes of the NAAS, Institute of Potatoes of the NAAS (IP of the NAAS), Institute of Agriculture of the Carpathian Region), the majority were resistant to pathogen 369 (57.7%) selection numbers, 104 (16.2%) were weakly resistant, 167 (26.1%) were unstable. All samples, which according to the results of the two-year laboratory and greenhouse tests were resistant, also showed a sign of resistance during the field test. Only 1 variety sample, which according to the results of laboratory and greenhouse studies was identified as resistant, turned out to be weakly resistant in field conditions. Two more varieties, which were considered weakly resistant according to the results of laboratory and greenhouse studies, turned out to be unstable in field conditions. One of them is tolerant. According to the results of yield accounting, all the studied 45 variety samples were divided into two groups: resistant (yield exceeds the control by 14—21%) and resistant and tolerant (yield exceeds the control by 58—102%). 25 cultivars are assigned to the resistant group, and 17 other cultivars are given the status of resistant and tolerant. Also, three more variety samples showed signs of tolerance, which turned out to be weakly resistant or unstable to G. rostochiensis (Ro-1). Conclusions. According to the results of the assessment of resistance to Globodera rostochiensis (Ro-1) of 640 samples sent from four breeding institutions, it was established that most of them (57.7%) were resistant to the pathogen, 16.2% were weakly resistant, and 26.1% were unstable. According to the results, the database of resistance screening of domestic breeding material to Globodera rostochiensis was supplemented. Together with the breeders of IP NAAS, a resistant and tolerant to this pathogen cv. Myroslava was created.